Physicochemical and cytotoxic properties of mixed palm oil-derived catanionic systems - Yong, Xiou Shuang (2020)
Versatility of surfactants marked its importance in industrial applications. Carboxylic acid derived from oleochemicals is one of the anionic surfactants. In order to diversify its applications, creating new compound with various functionality such as thermal behaviour and surface activity from the existing carboxylic acid is essential. Catanionic surfactant, the new class of surfactant, is attracting much interest due to its superior physicochemical properties. Some catanionic systems even show anti-cancer activities which is making a breakthrough for cancer treatment. The current study aimed to produce catanionic surfactants systems having palm oil-derived materials such as carboxylic acid and to explore some of their physicochemical properties (thermal behaviour and surface activities) and cytotoxicity. Catanionic surfactants systems having different degrees of chain length asymmetry were prepared from cationic quaternary ammonium surfactants (alkyl chain lengths of 12- to 18-carbon) and anionic palm oil-derived carboxylic acids (alkyl chain lengths of 8- to 18-carbon), respectively. The characteristics of neat catanionic surfactants using Fourier Transform Infrared (FTIR) and X-ray diffraction (XRD) confirmed the formation of catanionic surfactants with crystalline structures. The produced catanionic surfactants displayed greater thermal stability with 10% of weight loss at 125.15°C to 216.29°C and up to six thermal phase transition as compared with the parent surfactants, respectively. Similarly, the total change in enthalpy (ΔH) and entropy (ΔS) of catanionic surfactants were higher than their parent surfactants, in the range of 44.32 kJ mol-1 to 157.15 kJ mol-1 and 119.07 J K-1 mol-1 to 409.68 J K-1 mol-1, showing higher thermal stability and changes of molecular motion in the formation of more disordered phase when subjected to heat. Noticeably, the total ΔH and ΔS were closely related with the degree of chain length asymmetry in catanionic surfactant. Surface properties of aqueous catanionic systems were investigated via surface tension measurement. The critical aggregation concentration (CAC) obtained for catanionic systems indicated better self-aggregation capability and ranged from 0.0004 mM to 2.130 mM, at least 70% lower than cationic parent surfactants. The feature was also supported by higher surface excess concentration (Гmax) of catanionic systems from 1.26 × 10-6 mol m-2 to 3.82 × 10-6 mol m-2 and lower minimum area per molecule (Amin) ranging from 43 Å2 to 131 Å2 that was induced by an effective area reduction of oppositely charged headgroups. Other than that, cytotoxicity of catanionic surfactants and their parent surfactants were tested on both normal fibroblast 3T3 and breast cancer MDA-MB-231 cell lines. Cytotoxicity of catanionic surfactants and parent surfactants was found to increase with their alkyl chain length. The C18TA18 possessed highest cytotoxicity with half maximal inhibitory concentration (IC50) of 5.9 μM ± 0.3 μM on normal 3T3 cell line and 4.0 μM ± 0.1 μM on cancerous MDA-MB-231 cell line. Incorporation of anti-cancer agent into C18TA18 was found to exert lower cytotoxicity on 3T3 cell line than the treatment with C18TA18 alone, the cytotoxicity was reduced by 1.8-fold to 4.6-fold. In conclusion, palm oil-derived catanionic surfactants exhibited enhanced physicochemical and anti-cancer activities, with C18TA18 incorporated with anti-cancer agents exhibited potential anti-cancer activities.